A platform for patient positioning and motion monitoring in ocular proton therapy with a non-dedicated beamline. (March 2019) - Via, Riccardo; Pella, Andrea; Romanò, Francesco; Fassi, Aurora; Ricotti, Rosalinda; Tagaste, Barbara; Vai, Alessandro; Mastella, Edoardo; Rosaria Fiore, Maria; Valvo, Francesca; Ciocca, Mario; Baroni, Guido
Highlights: A general-purpose beamline was adapted to treat intraocular tumors with proton. Novel strategies for patient positioning and motion monitoring were applied. The proposed technologies comply with the strict accuracy requirement of ocular proton therapy. The results show accuracy in patient positioning comparable to centers equipped with dedicated technologies. Abstract: Purpose: At Centro Nazionale di Adroterapia Oncologica (CNAO, Pavia, Italy) ocular proton therapy (OPT) is delivered using a non-dedicated beamline. This paper describes the novel clinical workflow as well as technologies and methods adopted to achieve accurate target positioning and verification during ocular proton therapy at CNAO. Method: The OPT clinical protocol at CNAO prescribes a treatment simulation and a delivery phase, performed in the CT and treatment rooms, respectively. The patient gaze direction is controlled and monitored during the entire workflow by means of an eye tracking system (ETS) featuring two optical cameras and an embedded fixation diode light. Thus, the accurate alignment of the fixation light provided to the patient to the prescribed gazed direction is required for an effective treatment. As such, a technological platform based on active robotic manipulators and IR optical tracking-based guidance was developed and tested. The effectiveness of patient positioning strategies was evaluated on a clinical dataset comprising twenty patients treated at CNAO. Results: According to experimental testing, the developed technologies guarantee uncertainties lower than one degree in gaze direction definition by means of ETS-guided positioning. Patient positioning and monitoring strategies during treatment effectively mitigated set-up uncertainties and exhibited sub-millimetric accuracy in radiopaque markers alignment. Conclusion: Ocular proton therapy is currently delivered at CNAO with a non-dedicated beamline. The technologies developed for patient positioning and motion monitoring have proven to be compliant with the high geometrical accuracy required for the treatment of intraocular tumors.